Legal Protection of Geographical Indications of Jepara Carved Furniture Products in Strengthening Jepara City Branding as World Carving Center - Syalis Mei Setiani; Ubaidillah Kamal (Annual Review of Legal Studies, 2025)
In the era of globalization and the ease of technology, this is good, but also worrying. Bringing local and international markets closer together, but also creating traditional barriers that can be biased by global market demands. So, what is the relationship between City branding and Intellectual Property Law, and legal protection for City branding and Jepara Carved Furniture products? It is hoped that this study can answer the importance of city branding in strengthening the image of a city in global market competition and the protection of intellectual property for superior products of a region with geographical indications. The method used in this study is qualitative research with a legal approach, with literature studies. City branding built by the city of Jepara has a positive impact on the introduction of its superior products, namely Jepara Carved Furniture Products, which have also been registered in Geographical Indications. This creates added value for consumers for the image and quality of products that must be met by Craftsmen. Although city branding does not yet have clear rules for Intellectual Property, the existence of Geographical Indications is still able to provide intellectual property protection for these communal products in Indonesia. Although the author hopes that there will be at least clear rules regarding Jepara city branding, like several other cities that already have their city branding logos with legal regulations in their regions. As well as the need for protection of geographical indications in the international world for international trade.